Evaluation of the modified Micro-ID system for identification of Enterobacteriaceae. - Buesching, W J (1979)
Micro-ID is a system designed to identify the Enterobacteriaceae by utilizing reagent-impregnated disks for 15 biochemical tests. Since its initial evaluations, the system has undergone modification in formulation and in its computer data base. In a dual-center evaluation, 306 isolates of Enterobacteriaceae were tested: 145 common and typical isolates at the Mayo Clinic and 161 unusual or atypical isolates at the Center for Disease Control. Each laboratory also exchanged 50 cultures to test the system's reproducibility. Micro-ID correctly identified 142 (98%) of the common clinical isolates and 123 (76%) of the unusual or atypical organisms. However, in this latter group, three species tested were not in the system's data base. When these organisms were deleted from the analysis, 138 of 146 (95%) of the unusual or atypical isolates were correctly identified. Analysis of the 100 isolates identified in duplicate revealed 93% reproducibility of genus and species identification and 62% reproducibility of octal code numbers. Of the 31 strains with the same identification but different code numbers, 74% differed in only one biochemical test.